Can steel slag remediate the key problems of Rice-Wheat Cropping systems in India? - Jayara, Alok Singh; Kumar, Rajeew; Pandey, Priyanka; Shukla, Pavan; Dixit, Aparna (Journal of Cereal Research, 2024)
Sustaining the plant nutrition demand and meeting the present challenges of increasing micro nutrient deficiencies, biotic and abiotic stress as well as bringing economics in cultivation are major challenges of the Rice Wheat cropping system in India which extends for over 10 mha in India.  Utilization of the industrial waste is one of the several strategies for giving comprehensive solution to these problems. Steel slag provides a low-cost opportunity which has potential to address these challenges. Steel slag is indispensable waste generated during the steel manufacturing process and its disposal is major problem for the industry and environment too.  However, steel slag is rich in nutrients including Si, Ca, Mg, P, Fe, Mn and S and makes it a good alternative nutrient supplement with fertilizers. Iron acts as alternate electron acceptor, thus, can reduce the generation of methane in rice fields. The silica content in slag can be beneficial in reducing the sodium stress and heavy metal stress in contaminated soils. It is also been reported to reduce the biotic stress in crop plants.